Choosing an effective mobile health application to help manage Type 1 Diabetes Mellitus effectively - Wafeequa Dinath; Martie Mearns (South African Journal of Information Management, 2019)
Background: The current era can be called a mobile health revolution as medical applications created for smartphones are flourishing in the market. Individuals living with Type 1 Diabetes Mellitus (T1DM) need to count carbohydrates, monitor blood glucose levels and determine insulin dosages.